(untitled) (International Journal of Engineering and Computer Science, 2014)
In last years an increasing attention and more importance are dedicated to research in the fields of alternative vehicles, fuel consumption economy and reduction of related emissions. As an option to conventional vehicles, an increasing attention is being paid to the integration of Electric Vehicles (EV) and PhotoVoltaic (PV) panels resulting in Hybrid Solar Vehicle (HSV), and pure Solar Electric vehicle (SEV). This paper extends writers’ previous works, and proposes a new generalized and refined model for Mechatronics design of pure Solar Electric Vehicles (SEV) and some considerations regarding design, modeling and control solutions. The proposed SEV system model consists of eight main subsystems, each subsystem, is mathematically described and corresponding Simulink sub-model is developed, then an integrated generalized model of all subsystems is developed and tested. The proposed SEV system model is developed to help in facing challenges in developing Mechatronics SEV systems, in particular; early identifying system level problems and ensuring that all design requirements are met, as well as, for research purposes and application in educational process. Model is developed to allow designer to have the maximum output data to to design, tested and evaluate overall SEV system and/or each subsystem outputs characteristics and response, for desired overall and/or either subsystem’s specific outputs, under various PV subsystem input operating conditions, to meet particular SEV system requirements and performance.The obtained results show the simplicity, accuracy and applicability of the presented models to help in Mechatronics design of SEV system.